Identification of a Novel Substance P–Neurokinin-1 Receptor MicroRNA-221-5p Inflammatory Network in Human Colonic Epithelial Cells - Fang, Kai; Sideri, Aristea; Law, Ivy Ka Man; Bakirtzi, Kyriaki; Polytarchou, Christos; Iliopoulos, Dimitrios; Pothoulakis, Charalabos (Cellular and molecular gastroenterology and hepatology, 2015)
Substance P (SP), a neuropeptide member of the tachykinin family, plays a critical role in colitis. MicroRNAs (miRNAs) are small noncoding RNAs that negatively regulate gene expression. We examined whether SP modulates expression of microRNAs in human colonic epithelial cells. We performed microRNA profiling analysis of SP-stimulated human colonic epithelial NCM460 cells overexpressing neurokinin-1 receptor (NCM460-NK-1R). Targets of SP-regulated microRNAs were validated by real-time polymerase chain reaction (RT-PCR). Functions of miRNAs were tested in NCM460-NK-1R cells and the trinitrobenzene sulfonic acid (TNBS) and dextran sulfate sodium (DSS) models of colitis. SP stimulated differential expression of 29 microRNAs, including miR-221-5p, the highest up-regulated miR (by 12.6-fold) upon SP stimulation. Bioinformatic and luciferase reporter analyses identified interleukin-6 receptor (IL-6R) mRNA as a direct target of miR-221-5p in NCM460 cells. Accordingly, SP exposure of NCM460-NK-1R cells increased IL-6R mRNA expression, and overexpression of miR-221-5p reduced IL-6R expression. Nuclear factor κB and c-Jun N-terminal kinase inhibition decreased SP-induced miR-221-5p expression. MiR-221-5p expression was increased in both TNBS- and DSS-induced colitis and in colonic biopsy samples from ulcerative colitis but not Crohn’s disease patients compared with controls. In mice, intracolonic administration of a miR-221-5p chemical inhibitor exacerbated TNBS- and DSS-induced colitis and increased colonic tumor necrosis factor-α, C-X-C motif chemokine 10 (Cxcl10), and collagen, type II, α 1 (Col2α1) mRNA expression. In situ hybridization in TNBS- and DSS-exposed colons revealed increased miR-221-5p expression primarily in colonocytes. Our results reveal a novel NK-1R-miR-221-5p-IL-6R network that protects from colitis. The use of miR-221-5p mimics may be a promising approach for colitis treatment.